Gasification of Torrefied Microalgae in an Entrained Flow Gasifier by Means of Aspen HYSYS - ÖZVEREN, UĞUR (My University, 2022)
Many thermochemical procedures are used to convert bio-based materialsintogaseous products, but gasification is a promising approach due to its high efficiency, availability of a variety of solid fuels, ability to produce at different capacities, and low levels of harmful emissions. For both economic and technical purposes, entrained flow gasifiers are widely preferred in large-scale applications, further, they have a greater cold gas efficiency and a carbon conversion rate nearly 100 percent. On the other hand, optimization of the gasification process is costly and time consuming; therefore, simulation programs are frequently used in process modeling. In this study, an entrained bed gasifier model was developed in Aspen HYSYS software, and a parametric study was performed. The results depicted that the optimum ER value for microalgal biochar gasification is 0.21 and the optimum temperature is 1200 °C.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)